The Impact and Perception of Cell Phone Usage in a Teaching Hospital Setting. (December 2020) - Caminiti, Courtney; Deng, Lily; Greenberg, Patricia; Scolpino, Anthony; Chen, Catherine; Yang, Ellen; Oleske, James M
Objective: To evaluate perceptions regarding cell phone use in a teaching hospital setting among health care providers, residents, medical students, and patients. Methods: Fifty-three medical students, 41 resident physicians, 32 attending physicians, and 46 nurses working at University Hospital completed a questionnaire about cell phone use practices and their perceptions of cell phone use in the hospital. Forty-three inpatients admitted to medical/surgical units at University Hospital were surveyed at bedside about their perceptions regarding physicians' cell phone use. Results: All health care providers identified cell phones as a risk to patient confidentiality with no specific group significantly more likely to attribute risk than another. Practitioners were identified as either primarily as inpatient or outpatient practitioners. Inpatient practitioners were significantly more likely to rate cell phones as beneficial to patient care than outpatient practitioners. Physicians were statistically more likely to rate mobile phones as beneficial to patient care as compared to nurses. Among the patient population surveyed, one quarter noted that their physician had used a cell phone in their presence. The majority of those patients observing practitioner cell phone use had reported a beneficial or neutral impact on their care.Significance: Perceived risk of cell phones to patient confidentiality was equal across health care providers surveyed. Physician and medical students were significantly more likely to rate cell phones as beneficial to patients' care than nurse providers. Patients indicated that their physicians used cell phones in their presence at low rates and reported that the use was either neutral or beneficial to the care they received.